PENGEMBANGAN EXPERIENCE (UX) DASHBOARD REPORTING DATA REVIEW USER PENGGUNA APLIKASI LAZADA - Arfiensa, Dandy; Sany, Ezrifal; Mulyati, Sri (Jurnal Manajamen Informatika Jayakarta, 2024)
This study aims to design a UX Dashboard for analyzing the user experience of the Lazada app. UX methods, such as data collection and user experience analysis, are integrated. Findings from data analysis are utilized to create a dashboard providing a comprehensive overview of user experience, covering navigation, product search, checkout processes, and customer support. The dashboard enables monitoring changes in user experience and evaluating the impact of improvements. The results are expected to offer valuable insights for the Lazada development team to enhance the application and contribute to understanding UX practices in the e-commerce context and the development of user experience dashboards.